Asymmetries of maximum trunk, hand, and leg strength in comparison to volleyball and fitness athletes - Mattes, K.; Wollesen, B.; Manzer, S. (The Journal of Strength and Conditioning Research, 2018)
Playing volleyball and corresponding training loads lead to specific strains and might result in asymmetric muscle pattern. The study aimed to identify volleyball-specific maximum bilateral strength asymmetries in comparison to fitness athletes. The cross-sectional study design compared an age-matched male volleyball group (n = 23; 27.9 ± 5 years) with a fitness group (n = 30; 26.3 ± 3 years). The participants performed an isometric maximum handgrip strength test followed by 2 isokinetic concentric maximum strength tests to determine the performance capacity of the axial trunk rotators (left-right) and bilateral leg extensors. Differences between groups and left-right side (within group) were proven by variance analysis with repeated measurements. There was a left-right difference with higher maximum forces for the rotation in the right direction in the volleyball group (p = 0.0058) but the group interaction effect was not significant after alpha error accumulation. The results of the leg press indicated a stronger left leg in the fitness group (nonsignificant) in comparison to the volleyball group. Overall, the volleyball group displayed symmetry in maximum handgrip and leg strength and asymmetry in trunk rotation with higher strength in right rotation. This asymmetry for the right trunk rotation showed a small effect size. The resulting asymmetry might be an adaptation to the volleyball techniques, but it remains unclear if this is a cause for or of injury. As a practical implication, the asymmetries should be examined to develop individualized strength training programs for both groups.